THE IMPLEMENTATION OF CHARACTER MAP STRATEGY IN TEACHING STUDENTS’ READING COMPREHENSION AT UPT SPF SMPN 17 MAKASSAR - Nindy Aidya; Hj. St. Haliah Batau; Rampeng Rampeng (THE ACADEMIC: ENGLISH LANGUAGE LEARNING JOURNAL, 2021)
The purpose of this study was to determine the effect and response of students to the application of the map strategy character on the reading comprehension ability of class IX UPT SPF SMPN 17 Makassar. This research applied a pre-experimental research in one class pre-test and post-test. The population of this research is class IX students of SMPN 17 Makassar in the academic year 2021/2022 which consists of 165 students. The researcher took one class as a sample in this study namely class IX which consisted of 33 students. The instrument of this research is a multiple choice test. The results of this study indicated that there is a significant increase in the average score of students' reading comprehension between the pretest and posttest. The mean score of students' reading comprehension increased from 64.24 in pre-test to 79.63 in post-test. This shows that by using the character map strategy the students' reading comprehension ability increases. So this shows that the hypothesis H_1 is accepted and of course the hypothesis H_0 is rejected. The researcher concludes that the effect of using character strategy as a teaching strategy in learning English improves students' understanding ability.